Edukasi Pencegahan Pencegahan Risiko Infeksi Dengan Batuk Efektif Dan Mencuci Tangan Di Ruang Penyakit Dalam Non-Infeksi Rumah Sakit Abdul Moeloek Provinsi Lampung - Eka Yudha Chrisanto; Rika Yulendasari; Marlina Agustina; Refsi Erpiyana; Asep Rahmat Hidayat; Alisah Rahmah Hidayah; Taufiq Sofa; Hesti Wulandari; Sastria Handayani (Institut Teknologi dan Bisnis Semarang, 2024)
Nosocomial infections are a complex problem for hospitals with high morbidity and mortality rates. Clean and Healthy Living Behavior (PHBS) is a series of practices learned and carried out consciously that enable individuals or families to maintain health and play an active role in achieving public health. To prevent the spread of infection, include washing your hands regularly with soap and clean water, complying with coughing and sneezing etiquette, avoiding direct contact with pets and wild animals, and avoiding coughing and coughing from respiratory diseases, such as: sneezing. The aim of this activity is to increase respondents' knowledge regarding preventing the risk of infection by coughing effectively and washing hands. It was found that respondents were very enthusiastic about listening to the material presented by the presenters. Washing your hands is a form of a clean and healthy lifestyle, such as cough etiquette which must be done anytime and anywhere